Young Somalis in Australia, the UK and the USA: an understanding of their identity and their sense of belonging - Kabir, Nahid Afrose (© 2014 Institute of Muslim Minority Affairs., 2019)
This article was published in the Journal of Muslim Minority Affairs [© 2014 Institute of Muslim Minority Affairs.] and the definite version is available at http://doi.org/10.1080/13602004.2014.939556. The Article's website is at https://www.tandfonline.com/doi/abs/10.1080/13602004.2014.939556.